The efficacy of intralesional metronidazole compared to intralesional glucantime in the therapeutic therapy of cutaneous leishmaniasis - Ghafoor Ullah; Tariq saleem; Farhad Ali (Journal of Pakistan Association of Dermatologists, 2022)
Objective To assess the effectiveness of intralesional metronidazole vs. intralesional glucantime in the therapy of cutaneous leishmaniasis. Methods Study design is Randomized controlled trial, conducted in the Department of Dermatology, Lady Reading Hospital, Peshawar from the 1st of February to the 10th of June 2020. A total of 60 patients of both gender with cutaneous leishmaniasis <3 months duration were included. 30 patients were in the intralesional metronidazole group (Group A) while 30 patients were in the intralesional glucantime group (Group B). Efficacy from both groups was noted. Results The participants age ranged in this study from 15 to 50 years, with Group A having a mean age of 30.700± 6.13 years and Group B with a mean age of 30.500 ±5.72 years. In this study Group A having mean disease period of 1.4000±0.49 months, while Group B had a mean disease period of 1.6000±0.46 months. In Group A, the mean weight was 66.63±8.21 kg, whereas in Group B, it was 69.066±9.59 kg. Efficacy was demonstrated in 26.7 percent of Group A patients against 73.3 percent of Group B patients (p=0.000). Conclusion In our study intralesional glucantime is more effective and safe in the treatment of cutaneous leishmaniasis. Despite the fact that metronidazole was found to be unsuccessful in this trial, we feel that the quest for a pain free, readily applied, and effective treatment modality with minimum adverse effects for the therapy of cutaneous leishmaniasis is essential. Key words Cutaneous leishmaniasis, intralesional metronidazole, glucantime.